Spore by satellite - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Spore is now broadcast daily on satellite, as part of a strategy to make it more widely and more quickly available, especially where the mails are slow, and normal Internet connections are poor. The magazine has been available on the Internet since...